آفاتُ الخطِّ في القراءاتِ القرآنيةِ وشواهدِ النَّحوِ العربيّ (القراءاتُ الشاذةُ والشواهدُ الشعريةُ أُنموذجًا) - Almurib, Dr. Ahmed Abdulkafi (Journal of Calligraphy, 2023)
These writers excelled in calligraphy and its refining, and so did the shops of Al-Warraqah and Al-Warraqin, who practice the profession of copying or writing, such as the grammarian judge Abu Saeed Al-Sirafi who used to transcribe ten papers before sitting in the Judicial Council. However, this profession suffers from the pests of calligraphy and writing, which leads to its texts and takes them out of what its owner wanted, and the most important of these pests is the scourge of correction and distortion. The one who examines this linguistic heritage will find that this scourge - I mean the correction and distortion - has befallen him in many places that need to be refined and reformed. This research presents examples of abnormal readings and the names of their readers, as well as samples of grammatical poetry evidence, which was infected by the correction in the font, and took it out of the intended meaning, which led to the violation of the linguistic or grammatical rule on which it was built. كانت العرب في جاهليتها تقدم الرواية على الكتابة، وتجعلها أعلى مقاماً، ثم آلت المكانة للكتابةِ من بعدُ؛ لتكون الصدارة للكاتب في وزارات الدولة ومجالس الخلفاء، ينبئك عن ذلك سيرةُ كتَّاب العصر العباسي، كعبد الله بن المقفع وسهل بن هارون، ويحيى البرمكي. وقد برعَ هؤلاء الكُّتابُ بالخطِّ وتجويده، وكذلك نشأت دكاكينُ الوراقة والوراقين، الذين يمتهنون مهنة النسخ أو الكتابة، كالقاضي الفقيه النحوي أبي سعيد السيرافي الذي كان ينسخُ عشر ورقات قبل جلوسه في مجلس القضاء. غير أنَّ هذه المهنةَ يعتريها من آفات الخطِّ والكتابةِ ما يودي بنصوصها ويخرجها عما أراده صاحبُها، وأهمُّ هذه الآفاتِ آفةُ التصحيف والتحريف.والناظرُ في هذا التراثِ اللغويِّ يجدُ أنَّ هذه الآفةَ – أعني التصحيف والتحريف - قد أصابته في مواضعَ كثيرة، تحتاجُ إلى تهذيبٍ وإصلاح. يعرضُ هذا البحثُ نماذجَ من القراءاتِ الشاذةِ وأسماءِ قُرِّائها، وكذلك نماذجُ من شواهدِ الشعر النحوية، التي أصابها التصحيف في الخط، فأخرجها عن المعنى المقصود، ما أدى إلى نقضِ القاعدة اللغويةِ أو النحوية التي بني عليها.